Non-destructive evaluation of isotropic plate structures by means of mode filtering in the frequency-wavenumber domain. (August 2020) - Purcell, Frederick A.F.; Eaton, Mark; Pearson, Matthew; Pullin, Rhys
Highlights: Multi frequency steady state Lamb wave excited in plate structure. Response map measured by Doppler laser Vibrometer. Filtered in frequency wavenumber domain with mode filter calculated around specific thickness. Thickness map calculated from Mode filter the maximises energy at given point. Abstract: Non-Destructive Testing (NDT) techniques are prevalent in the aerospace, green energy and automotive industries. These techniques, including ultrasound, despite their use, still have limitations surrounding speed and resolution. This work presents the development of a band-pass mode filtering technique in the frequency wavenumber domain for the purpose of damage detection in isotropic materials. Data was captured in the temporal and spatial domain using a 3D Scanning Laser Doppler Vibrometer (SLDV) with piezoelectric transducers exciting the structure with a variety of steady state signals ranging in frequency from 75 kHz to 400 kHz and a frequency modulated signal from 75 kHz to 400 kHz. A thickness map was created based on the frequency and wavelength of the A 0 Lamb wave mode. The technique was demonstrated on two aluminium specimens with dimensions of 400 mm by 400 mm with a thickness range of 0.5 mm to 8 mm with distinct geometric features. Through using multi-frequency excitation combined with mode based filters an estimation of thickness was achieved with a mean percentage thickness error of 15%. Circular thickness reductions with a diameter of 10 mm were clearly identified at the maximum plate thickness of 8 mm. This technique was shown to perform better than wavenumber filtering by allowing data from multi frequency steady state excitation to be combined into a single resulting thickness map. This improvement was shown to be particularly important at greater thicknesses.